Case report: Experience and insights on the treatment of two cases of cryptococcal meningitis during the later stages of the COVID-19 pandemic - Zhou, Yuli; Qiu, Bingfeng; Jiang, Jun; Chen, Tianwen; Wang, Liqian; Yang, Yunxing; Ruan, Senlin; Chen, Yanlei; Fang, Huanli; Jin, Juan; Yang, Nan (Frontiers in Immunology, 2024)
In the late stages of the COVID-19 pandemic, there's an increasing trend in opportunistic infections, including bacterial and fungal infections. This study discusses the treatment process of two cases of cryptococcal meningitis during the COVID-19 pandemic. It highlights the importance of laboratory testing for these co-infections and stresses the need for vigilance, early diagnosis, and proactive treatment to improve patient outcomes in the post-pandemic era.